2009
DOI: 10.1186/1478-4491-7-34
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness study of caesarean-section deliveries by clinical officers, general practitioners and obstetricians in Burkina Faso

Abstract: BackgroundThe aim of this paper was to evaluate the effectiveness and cost-effectiveness of alternative training strategies for increasing access to emergency obstetric care in Burkina Faso.MethodsCase extraction forms were used to record data on 2305 caesarean sections performed in 2004 and 2005 in hospitals in six out of the 13 health regions of Burkina Faso. Main effectiveness outcomes were mothers' and newborns' case fatality rates. The costs of performing caesarean sections were estimated from a health sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 8 publications
0
77
1
Order By: Relevance
“…There was research evidence about nonprofessional health providers being associated with a higher in-country (and rural) retention rate, cheaper training cost and lower costs for employment (Lehmann et al, 2009;Dovlo, 2004). Furthermore, studies that compared clinical skills between professional and nonprofessional clinicians demonstrated a similar success rate in surgeries carried out by clinical officers, who are technician equivalents to surgeons (Hounton et al, 2009;Chilopora et al, 2007).…”
Section: The Skills Discourse In Pharmacy Educationmentioning
confidence: 94%
See 1 more Smart Citation
“…There was research evidence about nonprofessional health providers being associated with a higher in-country (and rural) retention rate, cheaper training cost and lower costs for employment (Lehmann et al, 2009;Dovlo, 2004). Furthermore, studies that compared clinical skills between professional and nonprofessional clinicians demonstrated a similar success rate in surgeries carried out by clinical officers, who are technician equivalents to surgeons (Hounton et al, 2009;Chilopora et al, 2007).…”
Section: The Skills Discourse In Pharmacy Educationmentioning
confidence: 94%
“…In practice, role transformation has been a struggle in many countries, including the industrialised ones, hence resulting in pharmacists reverting to a dispensing role in many cases. Many pharmacists therefore felt their skills were under-utilised (Humphrys and O'Brien, 1986).…”
Section: The Skills Discourse In Pharmacy Educationmentioning
confidence: 99%
“…Many African and Asian countries have successfully invested in these workers. [12][13][14][15] Our aim was to test the hypothesis that mid-level health workers are as effective as higher level health workers at providing good quality care in priority areas of the health service. We also hoped to increase understanding of their effectiveness and of how they can best be integrated into national healthcare systems.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Huicho et al (2008) showed that health workers with shorter training performed at least as well and sometimes substantially better than those with longer training in assessing, classifying, and managing episodes of routine childhood illness and in counseling the children's carers in Bangladesh, Brazil, Tanzania, and Uganda. On the other side, Hounton et al (2009) found significantly higher newborn case fatality rates when cesarean section was performed by clinical officers rather than by obstetricians and general practitioners.…”
Section: Evidence Of the Effects Of Skill MIX Changementioning
confidence: 84%